Effect of Modifying Net Height and Court Size on Children's Badminton Performance - Pathmanathan K. Suppiah; Abdul Muiz Nor Azmi; Low, Jeffrey Fook Lee; Hasnol Noordin; Md Safwan Samsir; Rabiu Muazu Musa (Horizon Research Publishing, 2024)
It may be possible for children to acquire motor skills more successfully and effectively if they are given equipment that is the right size for their physical characteristics. The study aims to examine the effect of modifying court size and net height on children’s badminton performance. Sixteen children aged 7 to 9 years (Mage = 8.3 years ± 1.4) participated in the study. They competed in a mini-match under four different situations where the court size or net height was modified. Children’s match-play performances in all conditions were notated and analyzed via video replay. The results from a repeated measure of two-way ANOVA showed that there was a significant interaction between court and net height on winning strokes, unforced errors, and strokes struck, p < .05. Nevertheless, there was no significant interaction between court and net height on rally length, hitting opportunities, and successful strokes, p > .05. The findings demonstrated that reducing court size and lowering net height led to an offensive playstyle where children recorded higher winning shots with fewer shots struck and unforced errors. Lowering net height also resulted in a shorter rally length and decreases in hitting opportunities. The current findings suggested that by reducing net height and court-size, skill acquisition can be enhanced among junior badminton players in match-play performance as the condition has improved children's success experience by producing more successful strokes during a match. These factors can be apart from being motivating factors that encourage decision-making in a realistic environment.